Informe practica Fenalco Antioquia (2013)
This plan is made up of practical tasks set by the organization, particularly the practice is based on assignment to work in the area of PROCRÉDITO. PROCRÉDITO is the central trade information and provides several benefits, one of these is the central platform and thence to Miscelleanous emerge which leads are monitored daily for good process and development. To comply with good performance and quality of service, is assigned some functions to meet during practice, be appointed later development opportunities to improve processes. The information given in compliance with the law PROCRÉDITO Habeas data, for better understanding, the law allows databases regularly and also sets some rules to keep in mind in proper handling of the acquired data. These databases are part of PROCRÉDITO, as stated earlier, is a powerhouse of information, thus in practice plan talks basics about databases and software engineering as it is to create a development choice to improve internal processes. Keywords PROCRÉDITO, Central of information, databases, software engineering, platform, habeas data law, flat files, systems.